Unsteady free convection of a stagnation point of attachment on an isothermal surface - D. B. Ingham; J. H. Merkin; I. Pop (International Journal of Mathematics and Mathematical Sciences)
The time development free convection flow near a three-dimensional stagnation point of attachment on an isothermal surface is studied at large Grashof numbers. A small time solution and an accurate numerical method is described for determining the solution of the time-dependent boundary-layer equations. For a range of values of parameter c, which describes the local geometry, the development of the various physical properties of the flow are calculated and compared with their values at small and large values of time. In another range of values of c the numerical results suggest the development of a singularity in the boundary-layer equations at a finite value of time. An anlysis is presented which is consistent with the numerical results and confirms the presence of this singularity.